PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IIIA SD NEGERI 021 TANJUNG PALAS KECAMATAN DUMAI TIMUR - Muda, Indra Muda Indra; Alpusari, Mahmud Alpusari Mahmud; ', Munjiatun (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract,The purpose of this study is to improve student learning outcomes in social studies in third grade SDN 021 Tanjung Palas Kecamatan Dumai Timur with TPS type of cooperative learning. This research is a form of action research collaborative. This study was performed using two cycles. The first cycle is done by implementing cooperative learning TPS type, whereas the second cycle performed after the first cycle of reflection. Stages at each cycle in this study contained: the planning phase, implementation phase, phase of observation and reflection stages. The results of data analysis in which the activity of teachers in the first cycle increased by 56% with enough categories increased by 32% to 88%, whereas for increasing student activity in the first cycle, 56% of the category quite well by 38% to 94%. For student learning outcomes obtained average at 57.69% pre-cycle, namely an increase in cycle I menjadai 79.10% and increased again in the second cycle becomes 87.94%. Frequency of students who completed the pre-cycle increased as much as 15% of students in the first cycle to 81% Siwa and second cycle to 100%. SMT type koopratif learning model to improve learning outcomes IPS third-grade students of SDN 021 Tanjung Palas Kecamatan Dumai Timur. Key word: Learning Cooperatif tipe TPS, Learning Outcomes IPS